"Is Omicron mild"? Testing this narrative with the mutational landscape of its three lineages and response to existing vaccines and therapeutic antibodies. Issue 8 (27th April 2022) - Rajpal, Vijay Rani; Sharma, Shashi; Kumar, Avinash; Chand, Shweta; Joshi, Lata; Chandra, Atika; Babbar, Sadhna; Goel, Shailendra; Raina, Soom Nath; Shiran, Behrouz
Abstract: SARS‐CoV‐2 Omicron with its lineages BA.1, BA.2, and BA.3 has triggered a fresh wave of Covid‐19 infections. Though, Omicron has, so far, produced mild symptoms, its genome contains 60 mutations including 37 in the spike protein and 15 in the receptor‐binding domain. Thirteen sites conserved in previous SARS‐CoV‐2 variants carry mutations in Omicron. Many mutations have shown evolution under positive selection. Omicron's giant mutational leap has raised concerns as there are signs of higher virus infectivity rate, pathogenesis, reinfection, and immune evasion. Preliminary studies have reported waning of immunity after two‐dose primary vaccine regime, need for the boosters, folds reduction in vaccine effectiveness and neutralizing antibodies even after boosting and significant neutralization resistance with the therapeutic monoclonal, polyclonal, and convalescent antibodies against Omicron. The narrative that "Omicron is mild, " therefore, needs time to be tested with a deeper, scientific dwelling into the facts.